Ni-kshay Poshan Yojana: receipt and utilization among persons with TB notified under the National TB Elimination Program in India, 2022 - Kathiresan Jeyashree; Jeromie W V Thangaraj; Devika Shanmugasundaram; G Sri Lakshmi Priya; Sumit Pandey; Venkateshprabhu Janagaraj; Prema Shanmugasundaram; Sabarinathan Ramasamy; Joshua Chadwick; Sivavallinathan Arunachalam; Rahul Sharma; Vaibhav Shah; et al. (Global Health Action)
Background Ni-kshay Poshan Yojana (NPY), a direct benefit transfer scheme under the National Tuberculosis Elimination Program (NTEP) in India, provides a monthly benefit of INR500 for nutritional support of persons with TB (PwTB). Objectives To determine the proportion of PwTB receiving at least one NPY instalment and pattern of utilisation; to ascertain factors associated with NPY non-receipt and association of NPY receipt with TB treatment outcome. Methods In our cross-sectional study, we used multi-stage sampling to select PwTB whose treatment outcome was declared between May 2022 and February 2023. A cluster-adjusted, generalized linear model was used to identify factors associated with the non-receipt of NPY and determine association between NPY receipt and TB treatment outcome. Results Among 3201 PwTB, 2888 (92.7%; 95% CI 89.8%, 94.8%) had received at least one NPY instalment, and 1903 (64.2%; 95% CI 58.9%, 69.2%) self-reported receipt of benefit. The median (IQR) time to receipt of first instalment was 105 (60,174) days. Non-receipt was significantly higher among PwTB from states with low TB score (aPR = 2.34; 95%CI 1.51, 3.62), who do not have bank account (aPR = 2.48; 95%CI 1.93, 3.19) and with unknown/missing diabetic status (aPR = 1.69; 95%CI 1.11, 2.55). Unfavorable treatment outcomes were associated with non-receipt of NPY (aPR 4.93; 95%CI 3.61,6.75) after adjusting for potential confounders. Conclusion Majority of the PwTB received at least one NPY instalment, but they experience significant delays. Most of the recipients utilised NPY for nutrition. Longitudinal follow-up studies are required to study the impact of NPY on treatment outcomes.